The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1808-657000882013
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de epidemia do mal das folhas em regiões de "escape" do Brasil

Abstract: In January and February 2013 occurred a SouthAmerican leaf blight epidemic in regions considered as escape zones, causing concern to rubber tree growers and throughout the rubber industry. A possible adaptation of the fungus to escape zones was raised and the consistency of disease control by the use of the binomial: plants with uniform renewal of leaves + dry season, typical of the escape zones, was questioned. The aim of this work was to bring relevant information to the rubber growers about the interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
1
Order By: Relevance
“…Therefore, temperature turns to a superfluous criterion. There are precedents for the temporary loss of immunity to SALB in some established Brazilian 'escape zones' due to unusually humid weather conditions [21], but cases relating to temperature anomalies have not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, temperature turns to a superfluous criterion. There are precedents for the temporary loss of immunity to SALB in some established Brazilian 'escape zones' due to unusually humid weather conditions [21], but cases relating to temperature anomalies have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1970s and 1980s, a series of programs encouraging natural rubber production (Programa de Incentivo à Produção de Borracha Vegetal-PROBOR) was conducted by the Brazilian government to increase national self-sufficiency, and although not successful, revealed that rubber trees could be grown in some areas of Brazil (mainly in some parts of São Paulo State) without being affected by SALB [21]. These "escape zones" are colder and experience an annual dry period that coincides with the refoliation period of the rubber trees [22].…”
Section: Introductionmentioning
confidence: 99%
“…Climatologically, SACZ system is responsible for the considerable amount of summer rainfall among the Central-West, Southeast, and part of North and Northeast regions, causing humidity accumulation during the summer, which must have favored such leaf blight epidemics at the beginning of the year in São Paulo, Mato Grosso do Sul, Mato Grosso, and Goiás States. On the other hand, the absence of this system causes drastic reduction in rainfall in these regions, consequently leading to losses in agricultural production and risk of water and energy rationing [13].…”
Section: Epidemiology Of South American Leaf Blightmentioning
confidence: 99%
“…As SACZ phenomenon is common in Brazil, new leaf blight epidemics are expected when a highly humid period coincides with the presence of new leaves in the rubber tree, since the pathogen is common, at low intensity, even in "scape" zones. The use of productive clones resistant to leaf blight is welcome, even for "scape" zones [13].…”
Section: Epidemiology Of South American Leaf Blightmentioning
confidence: 99%
“…Rubber trees are cultivated in the southeastern and centralwestern regions of Brazil to attend to high commercial demands for natural rubber, but also to escape from the fungal disease known as South American leaf blight caused by Microcyclus ulei (Henn.) Arx, which attacks plants in the Amazon region (6). One of the problems linked to the cultivation of H. brasiliensis (7,8) in these new areas (known as escape zones from the leaf fungus), however, is the presence of regions with warm frontand/or irregular rainfall regimes that impose water stress conditions (5).…”
Section: Introductionmentioning
confidence: 99%